Pain, Speech and Silence in Prudentius "Peristephanon" 5 and 9 - Clarke, Jacqueline (Vigiliae Christianae, 2020)
This article explores the relationship between pain, speech and power in Prudentius' Peristephanon. Two poems are selected for a focused analysis: Perist. 5 in which the martyr speaks at length, engaging in a rhetorical contest with his persecutor, and Perist. 9 where the martyr speaks briefly once to encourage his tormentors. By analysing these poems and comparing them with other poems in the Peristephanon, the article shows how martyrs can use speech to transcend pain and transfer suffering to their persecutors but also how silence can be as effective a weapon in their power struggle. Attention is also given to the role which the poet-narrator plays in both poems and the ways in which Prudentius employs his own narrative voice when his martyrs either cannot or do not wish to speak for themselves.